ISLAM RAHMAH DAN WASATHIYAH (Paradigma Keberislaman Inklusif, Toleran dan Damai) - Usman, Abd Malik (Universitas Negeri Yogyakarta, 2015)
Abstract.Islamic doctrines that brings mercy for the worlds (rahmatan lil'alamien) and itsadherents as moderate people (ummatan wasathan) as well as the best people is thebasis for the realization of the attitudes and behavior of Islam which is humanist,inclusive, tolerant and peaceful. In the context Indonesia that it is pluralistic society inthe field of customs, language, culture and even religion, Islam people (muslim) as themajority must perform as best people who are capable as grace and a paste for theplurality of Indonesian and to lead them for reaching prosperity for all mankind.Keywords : Islam, inclusive, grace, moderate, plurality.AbstrakDoktrin Islam sebagai agama yang membawa rahmat buat semesta alam (rahmatanlil